Epigenomic pathways from racism to preterm birth: secondary analysis of the Nulliparous Pregnancy Outcomes Study: monitoring Mothers-to-be (nuMoM2b) cohort study in the USA to examine how DNA methylation mediates the relationship between multilevel racism and preterm birth in black women: a study protocol - Goleen Samari; Yihong Zhao; Veronica Barcelona; Mitali Ray; Haotian Wu; Paolo Reho; Rebecca McNeil; Uma M Reddy (BMJ Open)
Introduction Preterm birth is a significant contributor to pregnancy-related morbidity and mortality, particularly affecting black women. Racism is a key driver of perinatal inequities, but mechanisms remain unclear. Epigenomics research offers promise in understanding how environmental exposures, including racism, influence gene expression and adverse pregnancy outcomes. We present our study protocol describing how we will investigate the interactive effects of individual- and structural-level racism on preterm birth within and across black and white women, characterise the blood-based methylome of black pregnant women and identify whether DNA methylation mediates the association between multilevel racism and preterm birth in black women.Methods and analysis We will conduct a secondary analysis of data from 6843 participants in the Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-be (nuMoM2b), a longitudinal, prospective cohort study (2010–2014). Individual-level racism was collected using the Experiences of Discrimination scale. Structural racism measures include racial residential segregation, income and racial polarisation, political participation, judicial treatment, homeownership and employment. These measures will be calculated using geocoded participant addresses and publicly available census data for black and white populations. Epigenome-wide methylation analyses will be conducted on stored DNA for all enrolled black women using the EPIC 2.0 BeadChip. Preterm birth was determined by abstraction from participant electronic health records. We will determine the joint effects of individual and structural racism on preterm birth, characterise DNA methylation profiles associated with preterm birth among black women and explore the mediating role of DNA methylation in the association between multilevel racism and preterm birth.Ethics and dissemination Study procedures were approved by the Columbia University Institutional Review Board (#AAAU0215). This study aims to fill critical knowledge gaps regarding the role of racism and epigenomics in preterm birth among black women.